2016
DOI: 10.1177/1524838016637080
|View full text |Cite
|
Sign up to set email alerts
|

Provider Screening and Counseling for Intimate Partner Violence: A Systematic Review of Practices and Influencing Factors

Abstract: Introduction: Intimate partner violence is a serious public health concern in the United States. Despite recommendations that physicians should routinely screen their patients, research has shown that lack of specific training has resulted in many health care professionals feeling unable to adequately perform this difficult but vital task. Though many educational resources exist to teach intimate partner violence screening, they often lack specific guidance on how to navigate this difficult conversation. In ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
97
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(107 citation statements)
references
References 71 publications
8
97
1
1
Order By: Relevance
“…Consistent with these results, IPV screening among general physicians has been associated with prior IPV training/education, perceived knowledge, and perceived preparation [19,20]. We also found that the percentage of obgyns who endorsed screening all patients at annual exams was consistent with existing research [20].…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Consistent with these results, IPV screening among general physicians has been associated with prior IPV training/education, perceived knowledge, and perceived preparation [19,20]. We also found that the percentage of obgyns who endorsed screening all patients at annual exams was consistent with existing research [20].…”
Section: Discussionsupporting
confidence: 86%
“…We also found that the percentage of obgyns who endorsed screening all patients at annual exams was consistent with existing research [20]. However, both physician endorsement and patient-reported data suggest that ob-gyns are still more likely to screen for IPV during new patient visits than during subsequent visits.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Participants in this study and others have emphasised the importance of providers knowing how to respond empathically to trauma disclosure. However, a recent systematic review on screening practices found that provider response to disclosure was only reported in two of 35 included studies (Alvarez, Fedock, Grace, & Campbell, ). The findings of the current study indicate that caring trauma history screening is especially important because patients who felt able to disclose their trauma histories to providers often also asked providers to tailor care in ways that met their needs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite multiple calls for clinic‐based screening and interventions to identify and support women victimized by partner violence, screening rates remain low . Health providers’ discomfort in addressing this topic is often cited for this lack of uptake .…”
mentioning
confidence: 99%